Technological, Pedagogical, and Content Knowledge of Teachers and Second Language Learning Motivational Orientation of Students - Bautista, Ed (JPAIR Multidisciplinary Research, 2021)
The study aimed to determine teachers' technological, pedagogical, and content knowledge and the second language learning motivational orientation of the College of Teacher Education students of the University of Mindanao. The study used a descriptive correlation research design, wherein survey questionnaires were administered among 300 freshmen students in the College of Teacher Education. The result disclosed that the level of TPACK of the teachers was very high as perceived by the respondents; also, the level of the second language learning motivational orientation of students was very high. Moreover, there was a significant relationship between the teachers' TPACK students’ second language learning motivational orientation. This means that both variables are gauged very high, and there is a correlation between the two variables. This would prompt educational institutions to hire English teachers based not only on their qualification but also on their competency and apt in honing and motivating English learners to master the English language.
Keywords: Education; TPACK; second language learning; motivational orientation; descriptive correlation design; Philippines